CORRELATION BETWEEN RISK AND RETURN OF STOCKS IN MULTISECTORS - . V , GEETHA; S , YAVANARANI.; N, MUTHUKUMAR. (International Journal of Psychosocial Rehabilitation, 2020)
Risk and return are both relevant to investment decisions. India has been an emerging nation and since liberalization, there have been a number of reforms that have witnessed stock market reactions. This has caused both the risk and return of the different sectors of the Indian market to frequently change and become unpredictable. There is no clear answer to whether the risks and returns of these indices remain stable over a period of time. Stock market ensures liquidity of industrial securities; it also ensures the appreciation of funds invested in the securities with the improvement in the performance of companies and increase in the demand for their securities. Thus they motivate the public to invest their savings in the capital of companies. These savings are channelized in the productive activities of the companies resulting in the capital formation which is essential for the economic development of a nation.